NARASI KEKERASAN DAN RESISTENSI DALAM NOVEL PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM (NARRATIVES OF VIOLENCE AND RESISTANCE IN THE NOVEL THE WOMAN WHO CRIED TO THE BLACK MOON) - Rakhyuni, Rakhyuni (Cahaya Ilmu Bangsa Institute, 2024)
This study examines the narrative of violence and resistance in the novel